Statistik Demografi Kumbang Predator Stethorus sp. (Coleoptera: Coccinellidae) pada Tetranychus Kanzawai Kishida (Acari: Tetranychidae) - Nirma Septia Ramlan Anjas; Sugeng Santoso; Ali Nurmansyah (Jurnal Entomologi Indonesia, 2021)
Tetranychus kanzawai is a species of mite that can cause agricultural crop losses of about 60–90%. One way to control pests that are environmental friendly is to use the predatory beetle Stethorus punctillum. This study aims to determine the demographic statistics, preferences, and functional response of S. punctillum on T. kanzawai. Observation of the S. punctillum biological using 100 eggs, observations were made of the number of individuals living until adult females produce offspring. Preferences of S. punctillum using 50 eggs and 50 nymphs and T. kanzawai adults, observations were made on the number of  T. kanzawai preyed by instar larvae I, II, III, IV, and S. punctillum adults. Functional response is done by giving S. punctillum prey as many as 30, 40, 50, 60, 70, 80 eggs T. kanzawai, observations made on the remaining number of eggs. S. punctillum eggs last for 7.01 ± 0.72 days. First instar larvae lasted for 4.84 ± 0.51 days, second instar 3.16 ± 0.52 days, third instar 3.00 ± 0.27 days, and IV instar 2.48 ± 0.50 days. Females lay eggs 64.47 ± 2.37 eggs. Gross reproduction rate (GRR) of S. punctillum 64.29 individuals/generation, net reproduction rate (Ro) of 17.18 individuals/female/generation, intrinsic accretion rate (r) of  0.27 individuals/female/day, average the generation period (T) is 62.41 days, and the double time (DT) is 2.51 days. The data shows that S. punctillum has a preference for T. kanzawai egg stages and type III functional response curves with Th 7.68 minutes and a 0.22 eggs/minute.